2018
DOI: 10.1111/petr.13278
|View full text |Cite
|
Sign up to set email alerts
|

Haematopoietic stem cell transplantation for mucopolysaccharidosis type VII: A case report

Abstract: Mucopolysaccharidosis type VII (MPS VII) is an inherited disease characterized by the cellular accumulation of undegraded GAGs due to the deficiency of the lysosomal enzyme β-glucuronidase. We describe a case of a 2-year-old female affected by a moderate form of MPS VII and submitted twice to HSCT with the aim of stabilizing skeletal problems and preventing neurocognitive alterations. The child underwent a second transplantation due to the rejection of the graft after a reduced-intensity conditioning in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Prior to the approval of vestronidase alfa, there were no disease-specific treatments for mucopolysaccharidosis VII, and disease management predominantly focused on symptomatic and supportive care (e.g. physiotherapy and hydrotherapy) [ 37 – 39 ]. BMTs have been performed in a small number of patients with mucopolysaccharidosis VII, some of whom experienced marked clinical improvements, especially in motor function, although effects on neurological manifestations were equivocal [ 7 , 38 – 40 ].…”
Section: Current Status Of Vestronidase Alfa In Mucopolysaccharidosismentioning
confidence: 99%
“…Prior to the approval of vestronidase alfa, there were no disease-specific treatments for mucopolysaccharidosis VII, and disease management predominantly focused on symptomatic and supportive care (e.g. physiotherapy and hydrotherapy) [ 37 – 39 ]. BMTs have been performed in a small number of patients with mucopolysaccharidosis VII, some of whom experienced marked clinical improvements, especially in motor function, although effects on neurological manifestations were equivocal [ 7 , 38 – 40 ].…”
Section: Current Status Of Vestronidase Alfa In Mucopolysaccharidosismentioning
confidence: 99%
“…HSCT is based on the supply of deficient enzymes through nondeficient GUS-producing hematopoietic cells and its derivatives like brain microglia [10]. To date, 10 cases treated with HSCT have been reported in patients with MPS VII [3,8,[11][12][13][14]; two of them underwent HSCT at a later stage, i.e., 7 and 12 years of age [3]. One patient was of unknown age, while the remaining seven underwent HSCT before 4 years of age [3,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Two long-term follow-up reports after HSCT were reported [3,13]. The case of transplantation at 2 years of age and retransplantation at the age of three and a half years had scoliosis but proper neurological development for six years [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allogeneic HSCT is recommended as a primary treatment for patients with MPS I [23,24] and MPS II [25,26], but has been debated within the field as a suitable treatment for MPS II [27]. Case studies have reported efficacy of HSCT in MPS IV [28], MPS VI [29], and MPS VII [30]. Issues of allogeneic HSCT include difficulties identifying suitable donors and risks of developing an immune response, i.e., graft-versus-host disease.…”
Section: Introductionmentioning
confidence: 99%